Knowledge of Pharmacy Department Students Poltekkes Kemenkes Medan About Vaccination Covid-19 - Zulfa Ismaniar Fauzi; Nurul Hidayah; Hilda Hilda; Masrah Masrah; Joice Putri Nababan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Corona Disease 19 is a coronavirus infectious disease with a high rate of transmission that primarily affects the respiratory tract. As a result, the Indonesian government established the COVID-19 immunization campaign in order to break the chain of transmission of the COVID-19 virus. Many are still afraid to get the COVID-19 vaccination due to the spread of information concerning harmful post-immunization occurrences. The goal of this study was to describe the level of student understanding regarding the COVID-19 immunization at the Pharmacy Department of the Medan Ministry of Health's Health Polytechnic. This is a descriptive survey that use the purposive sampling approach. The total population is 261 people, and the sample size is 158 people. A questionnaire that had already been validated was distributed using the Google Form in order to collect the data. The findings revealed that the average knowledge of vaccination fundamentals (72.6%), vaccine kinds (75.44%), and requirements and stages of the COVID-19 immunization (74.94%) was in a category of reasonable quality. Even though the level of knowledge about the purpose of vaccination is in the good category (91.89%). In generally, the description of the level of student knowledge about the COVID-19 vaccination at the Pharmaceutical Department of the Medan Ministry of Health Polytechnic is in the good category (78.98%). It is expected that even this factual information will inform and encourage the public to take part in COVID-19 immunization campaigns. Keyword: Covid-19, Immunization, Knowledge, Pharmacy, Student